PERANCANGAN SISTEM PAKAR DIAGNOSIS PENYAKIT IKAN AIR TAWAR MENGGUNAKAN METODE FORDWARD CHAINING BERBASIS WEB PADA UPTD BALAI BENIH IKAN DUKUPUNTANG KABUPATEN CIREBON - adjie priyatna; Jaya, Suhana Minah; Imam, Muhamad (INTI TALAFA, 2024)
An expert system is a computer-based application that is used to solve problems as obtained by experts. The aim of designing and building a web-based Design expert system is to facilitate and make it easier to diagnose fish diseases at the Dukupuntang fish seed center, Dukupuntang District. Cirebon. Because currently the uptd of the Dukupuntang fish seed center, Kabupaten Cirebon does not yet have the means to detect and diagnose fish diseases efficiently. To diagnose fish diseases, the majority currently still use manual methods by looking with the naked eye for the characteristics of diseased fish, then carrying out lab tests which take a long time to diagnose the disease. fish so that it is not optimal in cultivating freshwater fish. This sometimes causes many losses, including many fish dying from fish disease due to manual diagnosis and handling. So a web-based expert system application was created as a means of making it easier to diagnose fish diseases at the Dukupuntang Regency fish seed center uptd. Cirebon. The website was created using the PHP programming language, the application interface was developed from the Bootstrap CSS Framework and the database was MySQL. Data collection techniques were carried out by means of observation, interviews and literature study, while the method used was RAD (Rapid Application Development). This web-based expert system application can provide information regarding various problems regarding fish diseases. This application allows users to see the symptoms of fish diseases, as well as solutions for treating fish diseases. Key words: Expert System, Website, Diagnosis, Disease, Fish.